Pope's Chapel United Methodist Church 47th Annual Homecoming, October 5, 2003 - (:unkn) unknown (Pope's Chapel United Methodist Church (Wilkes County, Ga.))
Pope's Chapel United Methodist Church 47th Annual Homecoming, October 5, 2003. Chuck Smith, pastor. Event program, with invitation and handwritten notes. Pope's Chapel First Methodist Church. Wilkes County, Georgia. United States.
1 electronic document. popes-chapel_program_20031005.pdf. 7 pages. 46174734 bytes (master).
Keywords: Church history; Congregational churches; Homecoming; Methodist Church--Anniversaries, etc.; Methodists; Pope's Chapel United Methodist Church (Wilkes County, Ga.); Programs (Publications); United Methodist Church (U.S.); Wilkes County (Ga.); Georgia; Asbury, Francis; Boyd, James W.; Bufford, Pearl; Bunch, Bridget; Bunch, Gena; Bunch, Steven; Bunner, John; Bunner, Linda; Burton, Debbie; Cash, M.T.; Chafin, David; Chafin, Elizabeth; Chafin, Malcolm; Combs, Hazel; Faulk, Nanci Norman; Faulk, Nancy Norman; Floyd, Ethel; Fortson, Benjamin Winn; Fortson, Robert K.; Harris, Lundye; Humphries, Thomas; Landrum, John; Neal, Augustus A.; Norman, Jimmy; Ogilvie, Hannah Rebecca; Pope, Henry; Pullen, Emmie; Pullen, Jim; Pullen, Thomas; Sale, David; Smith, Chuck; Smith, George; Stephens, Helen; Wheatley, Jimmy; Wheless, Julia; Wiggins, Tom; Willingham, Robert (Skeet)